UPAYA MENINGKATKAN KEMAMPUAN MEMBACA NYARING SISWA KELAS III MELALUI PENDEKATAN KOOPERATIF TIPE PAIR READING - Alfiana; Dwi Permata Sari; Muhammad Akhir (STKIP Subang, 2025)
This research aims to analyze the effectiveness of implementing the Pair Readingcooperative approach as an intervention to improve the loud reading ability of third- grade students at UPT SD NEGERI 75 BENTANG. Loud reading is a fundamentalskill that requires specific strategies, which, based on previous findings at the researchlocation, still require improvement. The Pair Reading approach was chosen toencourage positive interaction, increase motivation, and provide immediate peerfeedback. This research uses a Classroom Action Research (CAR) design. The resultsare expected to show a significant increase in students' pronunciation, intonation, andloud reading fluency as a result of the implementationofPairReading